2023
DOI: 10.1038/s41598-023-41735-9
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow classification by employing various machine learning models for peninsular Malaysia

Nouar AlDahoul,
Mhd Adel Momo,
K. L. Chong
et al.

Abstract: Due to excessive streamflow (SF), Peninsular Malaysia has historically experienced floods and droughts. Forecasting streamflow to mitigate municipal and environmental damage is therefore crucial. Streamflow prediction has been extensively demonstrated in the literature to estimate the continuous values of streamflow level. Prediction of continuous values of streamflow is not necessary in several applications and at the same time it is very challenging task because of uncertainty. A streamflow category predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Through a comprehensive consideration of the research in related fields [40,46], we selected five widely used evaluation metrics, namely Intersection over Union (IoU), mean Intersection over Union (mIoU), precision (P), recall rate (R), and F1-score as evaluation metrics. IoU and mIoU were used to evaluate the performance of the model in terms of target spatial positioning and boundary accuracy, while the precision and recall rate was used to evaluate the ability of the model to accurately predict the flood area and successfully identify the real flood area for the flood detection task.…”
Section: Experimental Metricsmentioning
confidence: 99%
“…Through a comprehensive consideration of the research in related fields [40,46], we selected five widely used evaluation metrics, namely Intersection over Union (IoU), mean Intersection over Union (mIoU), precision (P), recall rate (R), and F1-score as evaluation metrics. IoU and mIoU were used to evaluate the performance of the model in terms of target spatial positioning and boundary accuracy, while the precision and recall rate was used to evaluate the ability of the model to accurately predict the flood area and successfully identify the real flood area for the flood detection task.…”
Section: Experimental Metricsmentioning
confidence: 99%
“…It is efficient and accurate, and it enables model visualization. AlDahoul N et al used various machine learning models to classify streamflow [12]. Khan et al used the support vector machine, naive Bayes, multilayer perceptron, and decision tree to classify students' early grades, and found that the decision tree classifier had high accuracy [13].…”
Section: Introductionmentioning
confidence: 99%